2014
DOI: 10.1139/cjfas-2013-0401
|View full text |Cite
|
Sign up to set email alerts
|

A peaked logistic-based selection curve

Abstract: Length-based selection curves define the relative catchability of fish to specific types of fishing gear, with catchability often highest at intermediate fish lengths. Distributions such as the normal, lognormal, or gamma are often used to define "peaked" selection curves, but these have limited capabilities to describe strongly asymmetric selection relationships, such as those sometimes observed for hooks or gillnets. Another, more flexible, peaked selection curve is proposed, which is derived by combining mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Generally, nets with thin ropes are considered more productive compared to the ones with thick ropes as they are less visible, easier to stretch and more flexible (Grati et al, 2015;Hamley, 1975, Jensen, 1995Turunen, 1996); accordingly, the findings of our study are similar to those of other studies. Our study has demonstrated that the same situation applies to the fyke nets used in crayfish fishing.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, nets with thin ropes are considered more productive compared to the ones with thick ropes as they are less visible, easier to stretch and more flexible (Grati et al, 2015;Hamley, 1975, Jensen, 1995Turunen, 1996); accordingly, the findings of our study are similar to those of other studies. Our study has demonstrated that the same situation applies to the fyke nets used in crayfish fishing.…”
Section: Discussionsupporting
confidence: 88%
“…We defined attraction as a function of distance between the natural and artificial reefs (closer reefs attract more fish) and of relative reef quality (higher quality artificial reefs will attract more fish). A logistic function (Smith and Taylor ) was used to define the amount of fish biomass in a given cell that is attracted to the artificial reef:Bri=BiBiQ01+elnfalse(992false)D99(DiD50)1where Bri is the relative biomass remaining in cell i after attraction, Q 0 is a reef quality parameter, D 99 is the distance over which almost all (99%) attraction occurs, and D 50 is the distance at which half the fish in a cell will be attracted a reef. D 99 was fixed at twice the value of D 50 to ensure a symmetric curve.…”
Section: Methodsmentioning
confidence: 99%
“…We defined attraction as a function of distance between the natural and artificial reefs (closer reefs attract more fish) and of relative reef quality (higher quality artificial reefs will attract more fish). A logistic function (Smith and Taylor 2014) was used to define the amount of fish biomass in a given cell that is attracted to the artificial reef:…”
Section: The Distribution and Attraction Of Fish Biomassmentioning
confidence: 99%
“…The monofilament net twine is more elastic and flexible than multifilament. Meshes of a more elastic twine can be stretched to be larger size by a struggling fish (Hamley, 1975). However, there was no systematic relation among the sizes of fishes captured in the same mesh-sized nets of the net types.…”
Section: Discussionmentioning
confidence: 94%
“…Horizontal hanging ratio (E) is defined as the ratio between the stretched head rope or lead rope relative to the total stretched netting mounted on that rope and it gives the distinctive shape of the mesh. It was shown that the hanging ratio is amongst many factors affecting the selectivity of fishes (Clarke, 1960 andHamley, 1975). However, the effects in selectivity of changing the hanging ratio are less studied than those of mesh size.…”
Section: Discussionmentioning
confidence: 99%